The role of language barriers on efficacy of rapid response teams. Issue 1 (1st January 2023) - Raff, Lauren; Moore, Carlton; Raff, Evan
ABSTRACT: Objectives: Rapid response (RR) systems are associated with decreased hospital mortality. Systemic biases and inequities can negatively impact RR outcomes. Language barriers between patients and providers are associated with worse outcomes, but it is unknown if language barriers are associated with RR outcomes. Methods: We analyzed all adult hospitalized patients who experienced a RR over one year (January 2020 to December 2020) at a tertiary care academic medical center. We used an objective scoring system to establish disease severity at the time of the event. We then compared disease severity and outcomes for patients who are primary language Spanish (PLS) and primary language English (PLE) using both univariable and multivariable analyses. Results: Of 1133 patients, 42 identified as PLS and 1091 as PLE. In multivariable analyses, PLS patients had significantly higher disease severity scores, as measured by deterioration index score (8.2, p = 0.021) at the time of their rapid responses. PLS patients also had 18.5% increase in length of stay (LOS) after RRs and this disparity was not mitigated when controlling for disease severity at the time of RRs. PLS was not a significant predictor for hospital mortality after RRs. Conclusions: Our study found that PLS patients had increased disease severity at the time of RRs and increased LOS after RRs. However, the disparity in LOS was not mitigated when controlling for disease severity at the time of RRs. These findings suggest that language barriers may cause both delays in activation of RR systems, as well as the care provided during and after RRs.